2017
DOI: 10.1016/j.bbabio.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of adiabatic primary electron transfer in photosystem I: Femtosecond spectroscopy upon excitation of reaction center in the far-red edge of the QY band

Abstract: The ultrafast primary charge separation in Photosystem I (PS I) excited by femtosecond pulses centered at 720 and 760nm was studied by pump-to-probe laser spectroscopy. The absorbance in the red edge of PS I absorption spectrum has an unusual exponential dependence on wavelength. The cutoff of short wavelength components of 760nm pulse allows direct excitation of reaction center chlorophyll molecules without involvement of light-harvesting antenna. The transient spectrum manifests the features of the primary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 80 publications
4
39
1
Order By: Relevance
“…We identi ed 28 photosynthesis-related DEGs between NaCl-treated and control plants (Additional le 5: Figure S5), leading to differences in oxygen releasing e ciency in petals between the two groups of S. salsa (Additional le 4: Figure S4). PSI and PSII are the main components of the photosynthetic apparatus in plants [56,57], including the proximal antenna of PSII (cp43) [79] and the PSI subunits PsaF and PsaN [58]. In the present study, DEGs related to photosynthesis, such as genes encoding PsbP and PsbR, were downregulated in NaCl-treated S. salsa owers (Fig.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We identi ed 28 photosynthesis-related DEGs between NaCl-treated and control plants (Additional le 5: Figure S5), leading to differences in oxygen releasing e ciency in petals between the two groups of S. salsa (Additional le 4: Figure S4). PSI and PSII are the main components of the photosynthetic apparatus in plants [56,57], including the proximal antenna of PSII (cp43) [79] and the PSI subunits PsaF and PsaN [58]. In the present study, DEGs related to photosynthesis, such as genes encoding PsbP and PsbR, were downregulated in NaCl-treated S. salsa owers (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…This complex is responsible for light harvesting and electron transport during photosynthesis immediately after water oxidation [56]. PSI, a chlorophyll-protein complex, catalyzes the transfer of electrons from plastocyanin/cytochrome c6 to ferredoxin/flavodoxin, a process driven by light [57]. The PSI subunits PsaF and PsaN interact with ferredoxin or plastocyanin [58].…”
Section: Degs Related To Antenna Proteins and Photosynthesis In S Samentioning
confidence: 99%
“…New data in isolated PSI complexes from cyanobacteria Synechocystis sp. PCC 6803 excited by femtosecond pulse at the far‐red edge of Q Y absorption band were recently obtained . In this work, the authors were able to show that excitation in the maximum of P 700 absorption generates electronic states with the highest contribution from P 700 *, whereas excitation in the far‐red edge predominantly generates charge transfer state P 700 + A 0 − in both branches of redox cofactors.…”
Section: Discussionmentioning
confidence: 66%
“…However, Refs. and have shown that after preferential excitation of P 700 and A 0 , formation of primary radical pair P 700 + A 0 − occurs, within 100 fs, and the formation of P 700 + A 1 − has a characteristic time of ~25 ps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation